Variation in outcome reporting in randomized controlled trials of interventions for prevention and treatment of fetal growth restriction. (2nd April 2019) - Townsend, R.; Sileo, F.; Stocker, L.; Kumbay, H.; Healy, P.; Gordijn, S.; Ganzevoort, W.; Beune, I.; Baschat, A.; Kenny, L.; Bloomfield, F.; Daly, M.; et al.
ABSTRACT: Objective: Although fetal growth restriction (FGR) is well known to be associated with adverse outcomes for the mother and offspring, effective interventions for the management of FGR are yet to be established. Trials reporting interventions for the prevention and treatment of FGR may be limited by heterogeneity in the underlying pathophysiology. The aim of this study was to conduct a systematic review of outcomes reported in randomized controlled trials (RCTs) assessing interventions for the prevention or treatment of FGR, in order to identify and categorize the variation in outcome reporting. Methods: MEDLINE, EMBASE and The Cochrane Library were searched from inception until August 2018 for RCTs investigating therapies for the prevention and treatment of FGR. Studies were assessed systematically and data on outcomes that were reported in the included studies were extracted and categorized. The methodological quality of the included studies was assessed using the Jadad score. Results: The search identified 2609 citations, of which 153 were selected for full‐text review and 72 studies (68 trials) were included in the final analysis. There were 44 trials relating to the prevention of FGR and 24 trials investigating interventions for the treatment of FGR. The mean Jadad score of all studies was 3.07, and only nine of them received a score of 5. We identified 238 outcomes across the included studies. The most commonly reported were birth weight (88.2%), gestational age at birth (72.1%) and small‐for‐gestational age (67.6%). Few studies reported on any measure of neonatal morbidity (27.9%), while adverse effects of the interventions were reported in only 17.6% of trials. Conclusions: There is significant variation in outcome reporting across RCTs of therapies for the prevention and treatment of FGR. The clinical applicability of future research would be enhanced by the development of a core outcome set for use in future trials. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.